Zgodovina podnebne znanosti - Coen, Deborah R. (Filozofski vestnik, 2025)
Standard histories of climate science have illustrated the long and distinguished pedi-gree of research on anthropogenic global warming. Such accounts focus on lone physi-cal scientists of the nineteenth and twentieth centuries who learned that burning fossil fuels might produce a warmer Earth but who were apparently ignored by their contem-poraries. This article will focus instead on elements that are missing from the standard narrative. It is organized around three historical trends that have indelibly shaped the science of climate: the theorization of human difference, empire-building, and industri-alization. The geographic focus is Europe and its colonies. Historical accounts of clima-te science that ignore its ties to European colonialism and racial capitalism risk shoring up a scientific culture that perpetuates these forms of oppression. The article begins by considering how the meaning of “climate” shifted between the early modern era and the nineteenth century in response to geographical accounts from European travelers and physicians and in conjunction with the transformation of the atmosphere into an object of laboratory study. The final section takes this history up to the present, tracing the legacies of colonialism into the era of digital climate models.
Keywords: climate change; colonialism; imperialism; imperializem; klimatske spremembe; kolonializem